Corporate Governance Failures Leading to Bankruptcy in State-Owned Enterprises (SOEs) Subsidiaries - Nabilla Mahva Tsabita; Ariawan Gunadi (Academia Open, 2025)
General Background: Good Corporate Governance (GCG) is essential for ensuring corporate integrity and preventing financial distress, particularly within State-Owned Enterprises (SOEs). Specific Background: Recent bankruptcy cases involving SOE subsidiaries reveal persistent weaknesses in transparency, accountability, and supervisory mechanisms, as exemplified by the collapse of PT Indofarma Global Medika (IGM). Knowledge Gap: Existing studies often assess fraud or GCG violations in isolation, lacking analysis that connects governance failures to legal and financial consequences within SOE parent–subsidiary structures. Aims: This study examines how suboptimal GCG implementation contributes to bankruptcy risks in SOE subsidiaries and evaluates the legal and managerial implications for parent entities. Results: Findings show that repeated fraud, inadequate risk management, and ineffective oversight created structural vulnerabilities that escalated into insolvency during the Suspension of Debt Payment Obligations process. Novelty: The research establishes a direct causal link between GCG failure and subsidiary bankruptcy within the specific legal framework governing SOEs, highlighting accountability gaps in parent–subsidiary governance. Implications: Strengthening GCG enforcement is critical to safeguard state assets, enhance supervisory effectiveness, and prevent future insolvencies in SOE corporate groups. Highlights: Suboptimal GCG implementation in SOE subsidiaries significantly increases bankruptcy risk. Parent–subsidiary governance gaps weaken supervision and allow fraud to recur. Strengthening risk management and accountability is crucial to protect state assets. Keywords: Good Corporate Governance, State-Owned Enterprises, Bankruptcy, Parent–Subsidiary Governance, Risk Management